(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The essay offers some reflections upon the article by Elisabetta Pulice on the evolution of medial professional ethics and upon the one by Cinzia Piciocchi on the definition and the limits of the right to conscientious objection. It aims at pointing out the connections between these two topics in the area of biolaw.